SMALL AND MEDIUM BUSINESS AS A MEMBER OF INTERNATIONAL STRATEGIC ALLIANCES - Vadym V. Tatarinov; Vadym S. Tatarinov; Valentina А. Pavlova (Akademičnij Oglâd, 2021)
The article considers the peculiarities of the construction and functioning of international strategic alliances and the reasons that hinder the participation of Ukrainian small and medium-sized businesses. Recommendations for the development of knowledge-intensive components of small and medium-sized businesses (venture, innovation and manufacturing businesses) and preparation for their participation in international strategic alliances are given: 1. In the conditions of globalization and strengthening of competition companies look for ways of saving of the economic efficiency, increase of competitiveness. One of such ways can be considered an international strategic alliance. ISA is an organizational agreement on long-term cooperation, which provides for the joint use of resources and management structures of two or more independent firms from different countries to implement tasks related to the mission of each of them; ISA is able to promote the innovative development of individual enterprises and the economy of a developing country as a whole; ISAs are an important link in the transfer of technology and other scientific and technical developments of national companies; SMEs with large companies may spread, on the one hand, due to the lack of financial and managerial opportunities for SMEs to develop business and compete with global players in the industry, and, on the other hand, large members of the alliance can count on the flexibility of SMEs and to obtain the results of their scientific and technical work, as well as the expansion of its scientific and technical base through mergers with SMEs or their acquisition; The highest achievement of ISA can be the creation of such innovations and modernization of production at a level that was not even laid down in the formation of the alliance. 2. In order to increase innovation activity, development and preparation of venture, innovation and production small and medium-sized businesses for participation in ISAs, the state must ensure after completion of quarantine: - increasing the investment attractiveness of Ukraine by maintaining political, economic stability and lasting peace in the country; - in the legislative order of creation and stimulation of the competitive environment in the field of venture, innovative and industrial small and average business in perspective branches of economy; – the possibility of using ways to diversify effective financial support for innovative enterprises based on the experience of developed countries; – stimulating bank capital to preferential financing of innovative SMEs in promising industries; – creation of a legislative basis for the development of the “angel network” in Ukraine; – obtaining a mandatory level of financial training through online education for start-ups in order to reduce the risk of using their financial support; – creation and development of regional infrastructure of resource, information, scientific and technical support for SMEs; – organization of training of high-class specialists in the field of support of venture business and organization of works on creation and realization of perspective projects; – sustainable development of the Ukrainian stock market; – improvement of the legal framework in terms of clarifying the functions and principles of venture funds and venture firms in order to eliminate their misuse of tax benefits; – protection of Ukrainian intellectual property abroad